Enrichment analysis of predicted effectors. - Aimilia-Christina Vagiona (17584758) (2025)
Left, negative predictions. Right, positive predictions. Colors from pink to grey indicate p-values from high to low; a lower p value suggests the proteins are more enriched in GO Biological Process and Molecular Function terms related to post-translational modifications. GO BP and MF terms are more enriched in the PTMs class, which supports the good performance of the model.